Combined Effects of Tanshinone IIA and an Autophagy Inhibitor on the Apoptosis of Leukemia Cells via p53, Apoptosis-Related Proteins and Oxidative Stress Pathways. (August 2022) - Song, Ying-Chyi; Kuo, Cheng-Chieh; Liu, Chuan-Teng; Wu, Tsai-Chen; Kuo, Yi-Ting; Yen, Hung-Rong
Background: Acute myeloid leukemia (AML) is a kind of hematopoietic malignancy with limited response and acquired resistance to therapy. Inducing apoptosis and inhibiting autophagy in tumor cells is a combinational strategy for the development of anticancer therapeutics. Tanshinone IIA (TAIIA) is one of the major ingredients in Salvia miltiorrhiza, which is the most prescribed herb for the treatment of AML in Taiwan. Therefore, this study aimed to delineate the anticancer effects of TAIIA and its effect when combined with an autophagy inhibitor to treat AML. Methods: The anticancer effects of a combination of TAIIA and the autophagy inhibitor 3-methladenine (3MA) on the human monocytic leukemia cell line THP-1 were explored. The apoptosis and cell cycle of the leukemia cells were examined by Annexin V and propidium iodide staining and analyzed by flow cytometry. The oxidative stress level was determined by a malondialdehyde (MDA) colorimetric assay, nitric oxide colorimetric assay and glutathione peroxidase (GPx) colorimetric assay. The expression of apoptosis-related proteins was determined by western blotting. Results: TAIIA treatment significantly induced apoptosis via increased p53, Bax/Bcl, PARP, and caspase-3 signals and oxidative stress by enhancing MDA and nitrate/nitrite production and reducing GPx activity in THP-1 cells in a dose-dependent and time-dependent manner. The combination of the autophagy inhibitor 3MA enhanced TAIIA-induced apoptosis via the p53, Bax/Bcl, PARP, caspase-3, and oxidative stress pathways in THP-1 cells. Conclusion: The results suggest that TAIIA and autophagy inhibitors have combined effects on the apoptosis of leukemia cells, thus representing a novel and effective combination with the potential for application as a clinical therapy for AML.